Antiseizure medication reduction and withdrawal in children with drug‐resistant epilepsy after starting the ketogenic diet. (15th August 2022) - Gogou, Maria; Pujar, Suresh; Nemani, Tarishi; Chiang, Chunyi; Simpson, Zoe; Hardy, Isobel; Schoeler, Natasha; Cross, J. Helen; Eltze, Christin
Abstract: Aim: To investigate the rate of successful withdrawal of antiseizure medication (ASM) after starting the ketogenic diet in children and identify predictive factors. Method: We retrospectively reviewed data of children with epilepsy, who were treated with the ketogenic diet for 6 months or longer at our institution, over a 5‐year period. We defined successful withdrawal of one or more medications as a time period of 3 months or more off this medication without restarting it or starting a new agent. Predictive clinical factors were investigated using binary multivariable logistic regression. Results: Seventy‐one children were included (28 females, 43 males; median age at seizure onset 5 months, median age at diet initiation 58.5 months, median duration of ketogenic diet 27.7 months). Reduction of one or more ASMs was attempted in 54 out of 71 (76%) children and was successful in 34 out of 54 (63%), including discontinuation of all ASMs in 13. Younger age at the start of the ketogenic diet was associated with higher odds of successful ASM withdrawal. ASM withdrawal was successful in 11 out of 19 children with less than 50% seizure reduction at 3 months. Interpretation: Reduction of ASM was achieved in two‐thirds of patients after the start of the ketogenic diet, where attempted, and can be successful even with little or unchanged seizure frequency while on the diet. Abstract : Antiseizure medication reduction and withdrawal in children with drug‐resistant epilepsy after starting the ketogenic diet.